Escola de tempo integral e ludicidade: os pontos de vista de alunos do 1º ano do ensino fundamental - Azevedo, Nair Correia Salgado; Betti, Mauro [UNESP] (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira, 2014)
This study is related to the expansion of elementary school in Brazil from eight to nine years, and the implementation of full-time education in the city of Presidente Prudente (São Paulo). The Cidadescola Program followed the guidelines proposed by the Ministry of Education, including the recommendation to enhance the fun and games. In this scenario, the objectives of this study are to understand the Cidadescola Program under the expansion of elementary education policies and the implementation of full-time school; to investigate the points of view of children on the activities undertaken in this context, paying special attention to the theme of playfulness. This is an ethnographic study, based on participant observation and on various strategies for the field data collection. It was found that children emphasize relationships among themselves and leisure practices that promote movement. In the case of the school studied, it was also concluded that there is a risk of an opposition between the regular shift of classes and the opposite shift of these classes, as if there were two different schools in the same school unit. However, didactic and pedagogical guidelines present in specialized literature and official documents, as well as the perspective of the children themselves, point towards the need for a full-time school, therefore, integrated.

Trata-se de um estudo relacionado à ampliação do ensino fundamental de oito para nove anos no Brasil e à implantação da educação integral no município de Presidente Prudente (SP), que recebeu o nome de programa Cidadescola e seguiu as diretrizes e orientações propostas pelo Ministério da Educação, entre as quais, a recomendação de valorizar os jogos e brincadeiras. Nesse cenário, os objetivos deste estudo são: compreender o programa Cidadescola no âmbito das políticas de ampliação do ensino fundamental e da implantação da escola de tempo integral; investigar os pontos de vista das crianças sobre as atividades desenvolvidas nesse contexto, com especial atenção ao tema da ludicidade. Trata-se de uma pesquisa etnográfica, que se valeu de observação participante e de várias estratégias para a coleta de dados em campo. Constatou-se que as crianças privilegiam as relações entre os pares e as práticas lúdicas em atividades que propiciam o movimento. Conclui-se também que, no caso da escola estudada, há risco de uma oposição entre o período regular e o contraturno, como se fossem duas escolas diferentes na mesma unidade escolar, enquanto as diretrizes didático-pedagógicas presentes na literatura especializada e os documentos oficiais, bem como a perspectiva das próprias crianças, apontam para a necessidade de uma escola integral, portanto, inteira.
Full-time school and playfulness: the points of view of 1st year students of elementary school
Keywords: infância; lúdico; educação integral; ensino fundamental de nove anos; childhood; playfulness; full-time education; 9-year elementary school